Developmental HCN channelopathy results in decreased neural progenitor proliferation and microcephaly in mice - Schlusche, Anna Katharina; Vay, Sabine Ulrike; Kleinenkuhnen, Niklas; Sandke, Steffi; Campos Martín, Rafael; Florio, Marta; Huttner, Wieland; Tresch, Achim; Röper, Jochen; Rüger, Maria Adele; Jakovcevski, Igor; Stockebrand, Malte; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
The development of the cerebral cortex relies on the controlled division of neural stem and progenitor cells. The requirement for precise spatiotemporal control of proliferation and cell fate places a high demand on the cell division machinery, and defective cell division can cause microcephaly and other brain malformations. Cell-extrinsic and-intrinsic factors govern the capacity of cortical progenitors to produce large numbers of neurons and glia within a short developmental time window. In particular, ion channels shape the intrinsic biophysical properties of precursor cells and neurons and control their membrane potential throughout the cell cycle. We found that hyperpolarization-activated cyclic nucleotide-gated cation (HCN) channel subunits are expressed in mouse, rat, and human neural progenitors. Loss of HCN channel function in rat neural stem cells impaired their proliferation by affecting the cell-cycle progression, causing G1 accumulation and dysregulation of genes associated with human microcephaly. Transgene-mediated, dominant-negative loss of HCN channel function in the embryonic mouse telencephalon resulted in pronounced microcephaly. Together, our findings suggest a role for HCN channel subunits as a part of a general mechanism influencing cortical development in mammals.
Gesehen am 22.03.2022
Published August 24, 2021